A gestão escolar como fator condicionante do grau de satisfação dos atores escolares e desempenho da unidade escolar - Igarasi, Lizarda Yae (2001)
The basic thesis of this work is that the school management constitutes a key factor for the quality of education in the school units, and therefore its main manager, the principal, assumes a main role in the school performance. Despite this fact, it has not been attributed to the educational management any priority in the educational management research in the educational area. Thus, this work aimed at investigating the influence on the style of management of the school administrator, so far as the principal is concerned. It was used bibliographical research on the subject and interviews carried out with professors, employees and directors of schools of the public system of education of the State of São Paulo. Amongst the most relevant results it was observed: 92% of the participant professors of the research consider that the performance of the principal influences the quality of education of the school; 93% of the participant employees of the research consider that they had had significant changes in relation to their activity, which resulted from for the varied forms of the directors' performance.